Inhibition of lysine methyltransferase G9a/GLP reinstates long-term synaptic plasticity and synaptic tagging/capture by facilitating protein synthesis in the hippocampal CA1 area of APP/PS1 mouse model of Alzheimer's disease - Han, Javan Lee Tze (BMC, 2022)
10.1186/s40035-021-00247-0